2001
DOI: 10.1097/00126334-200104150-00018
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Genotypic and Phenotypic HIV-1 Drug-Resistant Strains Among Patients Receiving Antiretroviral Therapy in Abidjan, Côte d'Ivoire

Abstract: To describe prevalence of antiretroviral (ARV) drug-resistant HIV-1 strains among patients with a history of earlier treatment with ARV drugs in Abidjan, Côte d'Ivoire, we determined mutations that confer HIV-1 ARV drug resistance by sequencing the viral reverse-transcriptase and protease genes derived from plasma viral RNA of 68 individuals consecutively enrolled in the Joint United Nations Program on AIDS Drug Access Initiative (UNAIDS-DAI) with a history of earlier ARV drug treatment in Abidjan between Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 15 publications
5
45
1
Order By: Relevance
“…These findings are consistent with previous studies that have reported similar rates of acquired drug resistance mutations in Cameroon (8,23) and other African countries with similar ART programs (10,31,32). The most prevalent mutations identified were M184V and K103N.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous studies that have reported similar rates of acquired drug resistance mutations in Cameroon (8,23) and other African countries with similar ART programs (10,31,32). The most prevalent mutations identified were M184V and K103N.…”
Section: Discussionsupporting
confidence: 93%
“…In countries where few patients are exposed to suboptimum treatment and a public-health approach is taken to HIV management, the potential for widespread viral resistance could be less likely than that in resourcerich settings. [42][43][44] Sentinel monitoring approaches to follow HIV resistance emergence in HAART programmes should be implemented where possible. 45 Our study presents several limitations mainly because it analyses the outcomes of an observational cohort with routine data monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that HIV pol can be efficiently amplified and genotyped from DBS collected from individuals with a wide range of plasma virus loads. These findings are important because genotypic testing from DBS may simplify drug resistance surveillance and monitoring in resource-limited settings (1,16,23). The establishment of efficient resistance surveillance networks in these settings represents an important public health tool that will help to assess the prevalence of HIV drug resistance and adjust treatment guidelines if needed.…”
Section: Discussionmentioning
confidence: 99%